(untitled) (Research, Society and Development, 2022)
Self-medication has become an activity with an accelerated increase in recent years. It is characterized by the use of medicines without a prescription by a duly qualified health professional. It is a very recurrent practice, which can be justified by the low quality of some health care, in addition to being a conduct that can provide self-care, minimizing symptoms and discomforts. In order to be safe in self-medication, drug users must receive greater knowledge about what they are acquiring in pharmacies, as well as the professionals of these establishments must be able to receive this orientation. This can prevent possible masking of symptoms, interactions or adverse drug reactions. The study is based on a literature review, which was based on scientific works already published between the years 2013 to 202 extracted from databases such as , Scielo, PubMed, and Google Scholar, being selected 25 articles that could address the theme, demonstrate justifications for its use, add situations in which self-medication can be used. Therefore, self-medication in the elderly is a common practice, however, with many chances of generating more serious health problems. As age advances, the prevalence of diseases common to the age group increases, which induces the use of polypharmacy. The objective of the study is to make the population aware of the risks of self-medication for health and to demonstrate the importance of the professional’s prescription for the use of medicines.